1997
DOI: 10.1038/sj.leu.2400734
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin-induced apoptosis in p53-null human leukemia HL60 cells and their isolated nuclei: effects of the protease inhibitors Z-VAD-fmk and dichloroisocoumarin suggest an involvement of both caspases and serine proteases

Abstract: The human leukemia cell line, HL60 is very sensitive to various B can activate CPP32, 13 and apoptotic activation of proteaapoptotic stimuli and p53-null. The death-related cysteine prosome 14,15 and cathepsin D 16 have been reported. A nuclear teases of the caspases family play a central role in the scaffold protease has been postulated to activate apoptotic execution phase of apoptosis, and we recently reported the nuclease(s). 17 Our previous studies in human leukemia HL60 importance of serine protease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 12 publications
1
59
0
1
Order By: Relevance
“…Thus, it is likely that AN34 is a cellular processing product of Ape1 after cleavage of Ape1 by a trypsin-like enzyme activated by caspase-3 during apoptosis. Several studies have reported that serine proteases may play a role in inducing chromatin DNA fragmentation during apoptosis (41)(42)(43). At the present time, the identity of the protease(s) involved in Ape1 processing and generation of AN34 remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is likely that AN34 is a cellular processing product of Ape1 after cleavage of Ape1 by a trypsin-like enzyme activated by caspase-3 during apoptosis. Several studies have reported that serine proteases may play a role in inducing chromatin DNA fragmentation during apoptosis (41)(42)(43). At the present time, the identity of the protease(s) involved in Ape1 processing and generation of AN34 remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the suppression of this apoptosis occurred exclusively among three wild-type p53 cell lines and not in two p53-null cell lines (Figure 4a and b). 1,[17][18][19][20] It is known that these three cell lines show p53-dependent apoptosis when stimulated by DNAdamaging agents. 1,17,18 In fact, these wild-type p53 cell lines showed the activation (accumulation) of p53 after the DNAdamaging treatments, and, as expected, the two p53-null cell lines did not (Figure 4d).…”
Section: Vanadate Suppresses P53-dependent Dna Damage-induced Apoptosismentioning
confidence: 99%
“…Camptothecin, a topoisomerase I inhibitor (reviewed in Rothenberg, 1997), was included in the study as an independent inducer of apoptosis (Del Bino et al, 1992;Shimizu and Pommier, 1997). We report that, although morphological and biochemical parameters of apoptosis, including PAI-2 cleavage, could be blocked by protease inhibition, the time course for commitment to cell death was not prolonged.…”
mentioning
confidence: 95%